Overconfidence in the Market for Lemons - Fabian Herweg; Daniel Müller (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
We extend Akerlof 's (1970) “Market for Lemons” by assuming that some buyers are overconfident. Buyers in our model receive a noisy signal about the quality of the good that is at display for sale. Overconfident buyers do not update according to Bayes' rule but take the noisy signal at face value. The main finding is that the presence of overconfident buyers can stabilize the market outcome by preventing total adverse selection. This stabilization, however, comes at a cost: rational buyers are crowded out of the market.
urn:nbn:de:bvb:19-epub-12411-7
Keywords: D82; L15; 330; Adverse Selection; Market for Lemons; Overconfidence; Adverse Selektion; Vertrauen; Prinzipal-Agent-Theorie; Verhaltensökonomik; Theorie